Sex determination, mating behavior and spawning frequency of captive wild blueband goby broodstocks, Valenciennea strigata - Choosri, Siriwan; Phuangsanthia, Wilaiwan; Pratoomyot, Jarunan (Food Agricultural Sciences and Technology, 2025)
This research was to examine the sex determination, mating behavior, and spawning frequency of captive wild blueband goby broodstocks, Valenciennea strigata, under laboratory conditions. The experiment was conducted over a 12 months period in a hatchery at Bangsaen Institute of Marine Science for a period of Chon Buri province, Thailand. Eight pairs of blueband goby broodstocks, derived from Chatuchak Market, Bangkok, were maintained in a biological recirculating system with tanks measuring 15 x 24 x 15 inches (70 liters of seawater). They were fed pelleted feed twice a day and supplemented with adults Artemia once a day for the duration of the study. Results revealed that the broodstocks had total weight ranging from 2.7 g to 19.4 g (average 5.8 ± 3.8 g) and total lengths between 7.1 and 13.8 cm (average 8.7 ± 1.5 cm) (n = 16). Sex determination showed that sex can be differentiated by the genital papilla: males have small sex polyps, and the females have rounded sex lobes, along with a more open anus compared to males. These secondary sexual characteristics may be helpful in sexing blueband goby. Blueband gobies use external fertilization with breeding behaviour occurred in the evening after sunset and taking about 45 minutes to complete the laying process. The eggs were adhesive and oval-shaped, with sizes ranging from 1.0 to 1.1 mm in length and 0.3 mm in width. The spawning occurred every 10 to 12 days (10 ± 0.89 days) (n = 7), and the number of eggs ranged from 3,604 to 34,000 eggs (n = 5). The embryonic period lasted 56 hours and 30 minutes after fertilization. This study provided fundamental data that can serve as a guideline for raising blueband goby and other marine gobiidae.